2024
DOI: 10.1093/nsr/nwae101
|View full text |Cite
|
Sign up to set email alerts
|

Surface-phonon-polariton-enhanced photoinduced dipole force for nanoscale infrared imaging

Jian Li,
Junghoon Jahng,
Xuezhi Ma
et al.

Abstract: The photoinduced dipole force (PiDF) is an attractive force arising from the Coulombic interaction between the light-induced dipoles on the illuminated tip and the sample. It shows extreme sample-tip distance and refractive index dependence, which is promsing for nanoscale infrared (IR) imaging of ultrathin samples. However, the existence of PiDF in the mid-IR region has not been experimentally demonstrated due to the coexistence of photoinduced thermal force (PiTF), typically one to two orders of magnitude hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Yet, in a recent paper, Li et al. show that, under certain conditions, it is the PiDF that prevails [ 4 ]. They observe that the Si–O–Si lattice vibrations of a quartz substrate can couple efficiently to the MIR field confined by the tip, forming a light–matter resonance mode known as a surface phonon polariton.…”
mentioning
confidence: 99%
“…Yet, in a recent paper, Li et al. show that, under certain conditions, it is the PiDF that prevails [ 4 ]. They observe that the Si–O–Si lattice vibrations of a quartz substrate can couple efficiently to the MIR field confined by the tip, forming a light–matter resonance mode known as a surface phonon polariton.…”
mentioning
confidence: 99%
“…at the nanoscale, PFIR has been applied in research across multiple fields, including energy materials, life sciences, photonics and so on. In previous studies, PFIR (the diagram of the apparatus is shown in Figure a and detailed procedures are described in Note 1 of the Supporting Information) has generally been considered to have a clear photothermal signal generation mechanism, while the signal of PiFM involves several entangled competing forces related to light excitation (optical gradient force, , photothermal expansion force, and photoacoustic force), which have been extensively analyzed, discussed, and decoupled. Figure b shows that the cantilever deflection curve within each PFT cycle carries oscillation signals that contain the sample’s infrared absorption information. Figure c shows a zoomed-in view of Figure b, focusing solely on the sample’s infrared absorption features, and it involves contributions from the three optical forces based on the same physical mechanism as PiFM, with photothermal expansion force playing a dominant role.…”
mentioning
confidence: 99%